The Image of the Trickster in the Novel by Vladimir Makanin The Underground, or the Hero of Our Time - Kovtun, Natalia (Literatūra, 2021)
The article is devoted to the study of the image of the trickster – one of the key ones in modern Russian culture and literature. The article analyzes the specifics of the functioning and attribution of the trickster figure in V. Makanin‘s novel The Underground, or the Hero of Our Time (1998). This is a soliloquium novel. It is shown how the appearance of the trickster hero, who is aware of his connection with the myth, helps to solve the tragic issues facing the consciousness of the turn of the XX-XXI centuries. The life – affirming, vital potential of the image of the main character of the novel – Petrovich is considered, the inherent possibilities, means of awareness and representation of the tragic are revealed. The paper examines the intertextual field of the character’s image, including the archetypes of “naked man”, “little man”, “extra man” and “underground man”, who made up the canon of Russian classics. The reinterpretation of archetypes is the realization of the author’s attempt, his hero, to “push” Russia into the next century, free from the dictates of the literary canon, opening up the prospect of finding one’s own Word as a self-determination of an individual in the new century.
Keywords: trickster; the duality; Makanin; iterary canon; The Underground, or the Hero of Our Time